Experimental and Numerical Assessment on S-shaped Diffuser performance with different Turbulence Intensity - Jessam, R. (Institute of Physics Publishing, 2020)
The turbulence structure in air intake S-shaped diffuser is proven to be influencing parameter on the diffuser performance. In the present research work, experimental and numerical investigations have been undertaken to explore the effect of inlet turbulence intensity level on the performance of air intake S-shaped diffuser. Detailed measurements including pressure and velocity at the inlet and outlet planes and static pressure on the top and bottom walls were taken at three pre-selected Reynolds numbers of 4.8Ã104, 6.4Ã104 and 7.5Ã104. The predicted corresponding turbulence intensities at the experimented three Re, were 4.16, 3.15 and 2.8. ANSYS-FLUENT 15 software with Standard k-Ïµ turbulence model has been used for numerical simulations. Numerical results of static pressure recovery, total pressure loss coefficient and wall static pressure recovery have been compared with the experimental results. The experimental results indicate that increasing Reynolds number at the inlet of S-shaped diffuser resulting in slight decrease in measured turbulence intensity. Also, as Re increased from 4.8x104 to 7.5x104, the static pressure recovery increased by 9 and the total pressure loss coefficient was reduced by 4.9. Â© Published under licence by IOP Publishing Ltd.